Knowledge Management Systems Based on Topic Maps Theory (Advances in Military Technology, 2017)
The aim of the paper is to summarize the experience gained from the research of the constructions of the Knowledge Management Systems (KMS) based on the ontology engineering. The heart of such a system is the ontology. Ontology is a term coined by traditional philosophers which gained recently a new meaning in computational sense. Computational ontologies are a means to formally model the structure of a system, to discover the entities and relations that emerge from its observation, and which are useful to the system purposes. There are currently two main formal approaches to construct ontology; Topic Maps and Resource Description Framework (RDF). In our projects we utilize Topic Maps theory and the tools based on this technology, e.g. ATOM2 as described in the paper. The key point of the solution is the ontology development; our methodology procedure is presented; the improvement of the methodology and the future research goals are oriented to automate the procedure steps. Phases of the methodology are collecting information sources and their processing utilizing the analytical software; clarification of the terms in the area in focus, selection of the candidate’s terms for ontology classes; verification of terms regarding the document base; ontology design and its verification. During the process the text mining tools (e.g. TOVEK) and other analytical tools are used. At the end of the paper the summary of the experience with the methodology application is presented
Keywords: knowledge management system; Topic Maps; ATOM; MENTAL; CEFME